Geração de biogás a partir da co-digestão de resíduos agroindustriais - Silva, Jayna Pessuto (My University, 2015)
The growth in agro-industrial and industrial activities becomes imminent problem concerning the disposal of waste generated in these activities. Currently, most of the waste generated is intended for industrial waste landfills and in the case of pig manure to esterqueiras due to environmental and economic viability. However, anaerobic digestion (AD) is a solution for treating waste being environmentally and economically feasible for the treatment of waste, as by microorganisms performs conversion of unwanted by-products in renewable energy. This study aimed to isolate, select and identify microorganisms capable of assisting in the conversion of agricultural and industrial waste into biogas. Rice residues, leather, pig manure (R) and (A), tannery sludge ETE and ETE UCS sludge were characterized by determination of organic carbon, total solids content before and after the degradation tests. The addition of an inoculum of microorganisms isolated from samples of larger volume of biogas generated were evaluated, however showed low molar fraction of methane. Thus, there was re-isolation of microorganisms from WWTP sludge samples during the UCS process showed 76% mole fraction of methane and 73,3mL accumulated volume of biogas. Successive isolation of microorganisms were performed in the mud, the first isolation was after 24 hours test with later isolation every 7 days a total of 5 isolates. The microorganisms were added to samples containing manure residue (A) and (R) pre-treated leather residues chemically and thermally, rice and rice residue with tannery waste sludge WWTP. It has been found that the addition of inoculum increased the mole fraction of methane from manure waste (A) (55%), manure (R) of 0.4 to 0.7. The sample of rice and tannery WWTP sludge generated a mole fraction of hydrogen approximately (1.0). Thus, it is concluded that the presence of microorganisms in the process is essential to the increase of the molar fraction of the gas of interest, since these produce enzymes capable of degrading wastes and convert them into energy in the form of biogas. The actual process of AD is characterized by the reduction of carbon, rice residue with addition of WWTP sludge tanning and adding inoculum greater reduction in carbon content (77.88%) and total solids content (90.34%).
O crescimento nas atividades agroindustriais e industriais torna eminente o problema referente à destinação de resíduos gerados nestas atividades. Atualmente, a maior parte dos resíduos gerados são destinados para aterros de resíduos industriais e, no caso de estercos suínos para esterqueiras devido a viabilidade ambiental e econômica. No entanto, a digestão anaeróbia (DA) é uma solução para o tratamento de resíduos, sendo ambiental e economicamente viável, pois através de microrganismos realiza a conversão de subprodutos indesejados em energia renovável na forma de biogás. O presente trabalho teve como objetivo isolar, selecionar e identificar microrganismos capazes de auxiliar na conversão de resíduos agrícolas e industriais em biogás. Os resíduos de arroz, couro, esterco suíno (R) e (A), lodo de ETE de curtume e lodo de ETE UCS foram caracterizados através da determinação de concentração de carbono orgânico, teor de sólidos totais antes e após os ensaios de degradação. A adição de inóculos de microrganismos isolados a partir das amostras que geraram maior volume de biogás foram avaliados, entretanto apresentaram baixa fração molar de metano. Assim, realizou-se novo isolamento de microrganismos provenientes de amostras do lodo de ETE da UCS que durante o processo de DA apresentou fração molar de 76% de metano. Foram realizados isolamentos sucessivos dos microrganismos presentes no lodo, o primeiro isolamento foi após 24h de ensaio e posteriormente foi realizado o isolamento a cada 7 dias totalizando 5 isolamentos. Os microrganismos isolados foram identificados como Bacillus toyonensys e B. thurigiensis e foram adicionados em amostras que continham resíduo de esterco (A) e (R), resíduo de couro pré-tratado quimicamente e termicamente, resíduo de arroz e resíduo de arroz com lodo de ETE de curtume. Verificou-se que a adição de inóculos aumentou a fração molar de metano dos resíduos de esterco (A) em (55%), esterco (R) de 0,4 para 0,7. A amostra de arroz e lodo de ETE de curtume gerou uma fração molar de hidrogênio de aproximadamente (1,0). Assim, conclui-se que a presença de microrganismos no processo de DA é fundamental para o aumento da fração molar do gás de interesse, visto que estes produzem enzimas capazes de degradar resíduos e transformá-los em energia na forma de biogás. O efetivo processo de DA é caracterizado pela redução dos teores de carbono, o resíduo de arroz com adição de lodo de ETE de curtume e adição de inóculo apresentou maior redução no teor de carbono (77,88%) e no teor de sólidos totais (90,34%).
Keywords: Biogás; Resíduos; Microbiologia industrial; Agroindústria; Biogas; Waste products; Industrial microbiology; Agricultural industries